Security analysis of stored contents in memory chip - Muhammad Afiq Sasman (2019)
The chip on smart cards stores sensitive information. An example of a smart card would be credit cards which stores data for the purpose of authentication and authorization when a transaction is made. Therefore, the chip should be secured to ensure that the data is protected from attackers. This project focuses primarily on hardware security. Side Channel Attack (SCA) in general is an attack on a device based on the data obtained from unintentional physical leaks. The objective of this project is to obtain the encryption keys from 2 smart cards via SCA. The power traces of the smart cards performing AES-128 encryption were recorded and analysed. The power traces were put through different power models and analysed at different points of the traces. The project has successfully obtained 16 out of 16 encryption keys from the AT Mega Card and 4 out of 16 keys from the UL Smart Card.